Mutational profiles of primary pulmonary adenocarcinoma and paired brain metastases disclose the importance of KRAS mutations. (December 2021) - Vassella, Erik; Kashani, Elham; Zens, Philipp; Kündig, Alexandra; Fung, Christian; Scherz, Amina; Herrmann, Evelyn; Ermis, Ekin; Schmid, Ralph A.; Berezowska, Sabina
Abstract: Background: Brain metastases present a significant complication in lung cancer with an unmet therapeutic need. Methods: In this single-centre, retrospective study, we genotyped a clinico-pathologically well-annotated cohort of consecutively resected brain metastases of lung adenocarcinomas and paired primary tumours, diagnosed from 2000 to 2015, using the Ion Torrent Oncomine Comprehensive Cancer Panel v3. Results: Among 444 consecutive brain metastases, 210 (49%) originated from lung cancer. Analysis was successful in 111 samples, including 54 pairs of brain metastasis and primary tumour. Most driver alterations were preserved in brain metastases. Private alterations exclusive to primary tumours, brain metastases or both sites (intersecting cases) were present in 22%, 26% and 26% of cases, respectively. Seven percent had no shared mutations. KRAS mutations were more frequent in primary tumours metastasised to the brain (32/55, 58%) compared to TCGA (33%, p < 0.005) and own data from routine diagnostics, independent from clinical or pathological characteristics. Fourteen cases showed alterations in the EGFR signalling pathway including additional KRAS alterations that were private to brain metastases. KRAS G12C was detected most frequently (26% of patients) and KRAS G12C and G13C variants were significantly enriched in brain metastases. Synchronous and metachronous cases had a similar mutation profile. Conclusions: Our results suggest an important role of KRAS alterations in the pathobiology of brain metastases from lung adenocarcinomas. This has direct therapeutic implications as inhibitors selectively targeting KRAS G12C are entering the clinics. Highlights: Molecular analysis of paired lung cancers and brain metastases puts focus on KRAS . KRAS alterations are more frequent in lung cancer with brain metastases. Additional KRAS alterations are a frequent event private to brain metastases. Among KRAS mutations, G12C and G13C variants are significantly more frequent.